Unraveling the ambiguity of the commonality element in Indonesian class action litigation - Susilo, Erwin; Nahdhah, Nahdhah; Negara , Dharma Setiawan (Scholar Center, 2026)
The meaning of commonality in Class Action (CA) lawsuits in Indonesia, which remains abstractly formulated, leaves room for judges to interpret it differently, potentially leading to